The Influence of Differentiate Learning and Student Learning Motivation on Nationalistic Insight of Elementary School Students - Asnawi Asnawi; Ary Kiswanto Kenedi; Dini Ramadhani; Tengku Muhammad Sahudra; Muhammad Rizki Wardhana (Jurnal Pendidikan dan Pengajaran, 2024)
This research arose because of the need to understand how differentiated learning affects the national insight of elementary school students. Differentiated learning is an approach that allows teachers to present learning material in different ways according to the needs and level of understanding of each student. This study aims to analyze the impact of differentiated learning and learning motivation on the national insight of elementary school students. This study used an experimental approach with a treatment design by level 2 x 2. The study participants involved 100 elementary school students. Nationality insight is measured through essay tests. Data analysis was performed using SPSS Vol 26 software, with analysis techniques including descriptive tests, prerequisite tests, and inferential analysis using the two-way ANAVA test. The results showed that there was a significant influence of the differentiated learning model on the national insight of elementary school students, as well as the positive influence of learning motivation on increasing the national insight of elementary school students. This study also found an interaction between differentiated learning models and student learning motivation towards the insight of nationality of elementary school students. The implications of this research can be used as a guide for elementary school teachers in developing students' national insights, by paying attention to differentiated learning factors and learning motivation.